The impact of teaching "Fractal Geometry " on developing the skills of creative thinking among students in the Mathematics Department at the College of Education- Sana’a University - AL- Moafaa, Ibrahim Mohmmed Qnaaf (Journal of Educational and Psychological Sciences, 2020)
This study aimed to prepare a course in Fractal Geometry, and to know its effect on developing creative thinking skills. The sample of the study consisted of (32) male and female students from the third level students at the Department of Mathematics, College of Education, Sana’a University, and the experimental method, one group, was used through the pre and post application of the experiment tool. For the purpose of data collection, a test was used in creative thinking Already prepared and the researcher has adapted it to the Yemeni environment, and the data was processed using SPSS package, by applying mono- variance analysis and t- test for two interconnected samples. The results resulted in the following: - There are statistically significant differences at the level of significance (α =0, 05) between the performance of the members of the experimental group in the pre and post application of the creative thinking test, and on each of its skills (fluency, flexibility, originality) and in favor of post- performance. - A large educational impact was achieved after teaching the proposed course on creative thinking in the study sample. The proposed course worked on developing the fluency skill at a higher rate than the rest of the skills of the students of the study sample. The researcher recommends that a fractal engineering course and its software should be included among the university courses